2014
DOI: 10.1111/vox.12163
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion indication predictive score: a proposed risk stratification score for perioperative red blood cell transfusion in cardiac surgery

Abstract: We derived a simple score that can be utilized to assess the need of blood transfusion in patients undergoing cardiac surgery. We are the first to report G6PD deficiency and history of cerebrovascular disease as predictors. We recommend prospective external validation of the proposed score on a larger cohort of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Such prevalence of inherited haemolytic anaemias may impact the transfusion requirements in our patients. We have recently observed that underlying G6PD deficiency is a risk factor for blood transfusion in cardiac surgery, and similar factor may play a part in explaining the difference in the effect of the cell salvage on the rate of allogeneic RBC transfusion . These findings infer the need for more studies in our region in patient blood management (PBM) during cardiac surgery.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Such prevalence of inherited haemolytic anaemias may impact the transfusion requirements in our patients. We have recently observed that underlying G6PD deficiency is a risk factor for blood transfusion in cardiac surgery, and similar factor may play a part in explaining the difference in the effect of the cell salvage on the rate of allogeneic RBC transfusion . These findings infer the need for more studies in our region in patient blood management (PBM) during cardiac surgery.…”
Section: Discussionmentioning
confidence: 91%
“…Cardiac surgery is a major procedure that is anticipated to require significant transfusion support that varies based on many predictors . Despite the presence of current guidelines of transfusion in cardiac surgery , there is a wide variation in the transfusion rates ranging from 40% to 90% .…”
Section: Introductionmentioning
confidence: 99%
“…Although preoperative assessment and identification of patients at risk of receiving a blood transfusion is necessary for the delivery of safe and effective care, as well as the coordination of healthcare resources, current information regarding the early identification of patients at risk of transfusion is lacking. In the clinical setting, serum haemoglobin levels are the most commonly used indicators to direct physicians regarding the potential need for blood transfusion.…”
Section: Introductionmentioning
confidence: 99%
“…All patients were transfused intraoperatively and postoperatively as per the previously described local transfusion and blood management protocols. 11,12 Intraoperative allogeneic RBC transfusion was performed aiming for a hematocrit (Hct) level of > 23%. The cell saver (CS) has been in routine use for all patients undergoing cardiac surgery in the hospital since 2010.…”
Section: Methodsmentioning
confidence: 99%